Implementación, organización y codificación del archivo de la unidad académica de ciencias administrativas y humanísticas de la Universidad Técnica de Cotopaxi - Carrera Chicaiza, Mayra Alexandra (2015)
Cotopaxi Technical University, is located in San Felipe, Eloy Alfaro Parish, Simon Rodriguez avenue; It is a guaranteed higher education institution; that struggle for the well-being of society , especially those low-income people, looking for a quality education and excellent, through efficiency and effectiveness achieved the requirements of the University community. Implementation, organization and coding has been developed with the purpose of leaving embodied innovative ideas, for the Department's archive the Academic Unit of Administrative Sciences and Humanistic of the Technical University of Cotopaxi, with the aim of reaching a management organization, conservation and effective excellent scanning; It is implementation of colors will allow expediting the search for records….